STANDARDISASI KULIT PISANG KEPOK (Musa paradisiaca L) SEBAGAI ALTERNATIF PENYEMBUH LUKA - Ariani, Novia; Kumalasari, Eka; Fawwazi, Muhammad Hafizh Abiyyu Fathin; Nayandra, Faizah; Purnomo, Dimas Kalinggo; Rahayu, Mirenne Anik Sri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Kepok banana peel (Musa paradisiaca) is an agricultural waste with great potential to be utilized as a raw material for traditional medicine. Several studies have demonstrated that kepok banana peel contains bioactive compounds that act as antioxidants, antibacterial agents, and accelerate the wound healing process. Standardization of the simplicia and extract is necessary to ensure quality, safety, and consistency of its effectiveness as a phytopharmaceutical. This study aims to standardize kepok banana peel through both specific and non-specific parameters. The extraction method employed in this research was sonication using ethanol as a solvent. The results showed that kepok banana peel contains active compounds such as alkaloids, flavonoids, and saponins. Standardization tests on the simplicia powder of kepok banana peel included determination of water content, total ash, acid-insoluble ash, ethanol-soluble extract, water-soluble extract, total plate count (TPC), yeast and mold count (YMC), and heavy metal contamination, with the following results: 10.34%; 9%; 2.25%; 0.06%; 6.91%; 10.26%; >3.0 × 10³ cfu/g; 5.7 × 10³; <0.001 mg/kg, respectively. Meanwhile, the standardization results for the kepok banana peel extract were as follows: 9.57%; 11.19%; 0.07%; 0.26%; 21.68%; 22.53%; 4.6 × 10³ cfu/g; 8.2 × 10³; <0.001 mg/kg.